Islamic Awakening and Its Role in Islamic Solidarity in Malaysia - Saodah Abd. Rahman (International Institute of Islamic Thought, 2012)
The Islamic Awakening in Malaysia has brought about the consciousness of adopting and practicing the Islamic way of life. The process of implementing the principles of Islam is based on a gradual evolutionary process, rather than a drastic approach. Therefore, the selective implementation of Islamic law has been carried out relatively smoothly. For that reason, various institutions have been established ‒ such as, Islamic universities, Islamic banking and insurance companies, and other Islamic organizations and institutions. The case studies in this article related to Malaysia are: The Pan-Malaysian Islamic Party (PAS), Angkatan Belia Islam Malaysia – ABIM (Malaysian Islamic Youth Movement), and some Islamic institutions, which play important roles in the Islamic Awakening and solidarity in Malaysia. The PAS and ABIM are the prominent Islamic parties and movements, respectively, which can be regarded as the driving force behind the Islamic Awakening in Malaysia. Based on a tridimensional perspective ‒ that is, socioeconomic well-being and the strength of the expansion of Islamic education, and political stability ‒ this study highlights the accomplishment of Islamic Awakening in Malaysia.